Prevalence and Impact of Psychiatric Co-Morbidity in Patients with Spinal Pathology in Basrah, Iraq - Alshawi, Mustafa Habeeb; Ahmed Hamdan, Professor Thamer; Weichert, Dr. Immo; Lui MCh, Daren F.; A. Mohammed Saeed, Dr. Mubder; Kyaw, Dr. Inzali (Clinical Medicine And Health Research Journal, 2024)
Background and objective: to minimize complications by proper selection of patients for surgery and to evaluate what is the impact of psychiatric co-morbidity in patients admitted to a spinal surgical unit in Basrah, Iraq. Patients and Methods: A multi-center cross-sectional prospective cohort study was conducted on 247 patients. In Basrah province. During admission complete history was taken in form of identity, complaint, past medical and surgical history, drug history, type of previous and the coming surgery and lastly special emphasis on the questioner to assess patient psychological status using the Patient Health Questioner. Somatic Anxiety Depressive Symptoms (PHQ.SADS) After one week and one-month the same questions were addressed to the patient to check the general condition,and any complications or readmission. Results: Out of the 247 patients: Eight patients refuse to be part of this study, thirty-one patients lost follow up, three patients excluded from the study due to exclusion criteria, five patients their surgery postponded because they were psychologically unstable and advised for psychiatrist consultation. 111 patients (55.5%) of the sample size were male patients. A 90 (45%) patients were at age of 38-57 years, 111 (55.5%) of the sample were male 82 patients (41%) were of moderate degree using the PHQ.SADS. 62 patients (31%) were within the severe scale PHQ.SADS.132 patients (66%) complained from radiculopathy with or without backache,192 (96%) patients discharged safely postoperatively. 41(39.4%) patients were diagnosed with lumber canal stenosis belongs to the severe group. Psychological break down occurs in 10 (5%) patients, 9 (90%) of those patients belong to severe grade category of PHQ.SADS. Conclusion: There was a strong association between pre-operative psychological conditions and post-operative complications in form of repeated visit after surgery and persistence of pain and disability.